Preliminary behavioral assessment of cagemates living with conspecifics submitted to chronic restraint stress in mice - Carneiro de Oliveira, P. E.; Zaniboni, Caroline R.; Carmona, Isabela M.; Fonseca, Aura R. [UNESP]; Canto-de-Souza, Azair [UNESP] (Elsevier, 2017)
The capacity of rodents to recognize and respond to emotional signs from a conspecific is a valuable adaptive behavior, which provides essential skills for species survival. However, repeated exposure to aversive situations may elicit maladaptive behavioral responses in subjects that experience noxious episodes and their colony members. Previous findings by our group demonstrated that living with a subject in neuropathic pain induces anxiogenic-like behaviors and hypernociception in mice. Whereas chronic pain may be considered a stressful stimulus, we extended our findings on stress-induced emotional transfer. For this purpose, we investigated whether cohabitation with a partner subjected to chronic restraint stress was able to promote alterations in anxiety-like behaviors, pain sensibility and defensive responses. Male Swiss mice were housed in pairs for 14 days and then separated into control, stress, and cagemate groups. The stress group was subjected to 14 days of restraint stress (1 h/day) in the presence of the cagemates, while the pair-housed control group was left undisturbed. A day after last stress session control, stress, and cagemate groups were evaluated using elevated plus maze test, writhing test, and rat exposure test. Results demonstrated that chronic stress attenuated weight gain in the stress group. Moreover, cohabitation with mice subjected to chronic restraint stress induced anxiogenic-like behaviors, pain hypernociception, and alterations in defensive responses in both cagemate and stress groups. These preliminary findings suggest that chronic exposure to aversive stimulus may induce behavioral alterations even in observers.
Keywords: Anxiety; Chronic restraint stress; Emotional contagion; Mice; Nociception; Rat exposure test